Community engagement in early childhood development intervention trials: lessons learnt from a stepping stones program in rural India - Syed, Zahiruddin Quazi; Telrandhe, Shital; Holding, Penny A.; Dudhkohale, Swati; Patil, Manoj; Umate, Roshan; Khatib, Mahalaqua Nazli; Gaidhane, Shilpa; Choudhari, Sonali G.; Saxena, Deepak; Gaidhane, Abhay (Frontiers in Public Health, 2025)
BackgroundDelivering Early Childhood Development (ECD) interventions in low-resource settings requires context-sensitive adaptive strategies grounded in community realities. The Stepping Stones Program, implemented in rural central India, sought to improve parenting practices and child development outcomes through structured community engagement. This paper presents the approach, implementation, and program impact, offering insights into building scalable, community-owned models for ECD.MethodsThis mixed-methods study was embedded within a cluster-randomized controlled trial conducted in 106 villages across two rural blocks in Maharashtra, India. A total of 656 pregnant women were enrolled and followed until their child reached 24 months. Intervention clusters received a responsive parenting and nutrition program integrated with existing Anganwadi services, while control clusters received standard government services. Community engagement was operationalized through participatory planning, the Photostory approach for initiating dialogue with the community, and the establishment of Curriculum Development Committees and a Community Engagement Board. A Monitoring, Evaluation, and Learning framework supported real-time adaptations. Process indicators were analyzed descriptively; child development outcomes were assessed at 24 months using mixed-effects regression models.ResultsThe program demonstrated strong community participation, with 85% of households engaging in at least one activity and 70% regularly attending sessions. Fathers’ participation in caregiving sessions increased from 4.3 to 33.65%. Balsakhis (local female volunteers) independently delivered over 80% of sessions. Integration with government systems was achieved through policy alignment and involvement of ICDS functionaries in program delivery. At 24 months, the mean difference of the development score in all domains between the intervention and control arm was statistically significant (p > 0.05). Children in the lowest wealth quintile showed the largest improvements in cognitive (effect size: 0.92, p < 0.001), motor (0.72), and language development (0.79). Children below the poverty line also showed significant gains across developmental domains.ConclusionStructured, participatory community engagement was critical to the successful implementation and impact of the Stepping Stones Program. The program evolved from a top-down intervention to a community-driven platform for nurturing care. Findings support the utility of an adaptive engagement framework in building equitable, sustainable, and scalable ECD interventions in low-resource settings.